Effects of Dietary Flavonoids on Reverse Cholesterol Transport, HDL Metabolism, and HDL Function(1)(2) - Millar, Courtney L (Adv Nutr, 2017)
Strong experimental evidence confirms that HDL directly alleviates atherosclerosis. HDL particles display diverse atheroprotective functions in reverse cholesterol transport (RCT), antioxidant, anti-inflammatory, and antiapoptotic processes. In certain inflammatory disease states, however, HDL particles may become dysfunctional and proatherogenic. Flavonoids show the potential to improve HDL function through their well-documented effects on cellular antioxidant status and inflammation. The aim of this review is to summarize the basic science and clinical research examining the effects of dietary flavonoids on RCT and HDL function. Based on preclinical studies that used cell culture and rodent models, it appears that many flavonoids (e.g., anthocyanidins, flavonols, and flavone subclasses) influence RCT and HDL function beyond simple HDL cholesterol concentration by regulating cellular cholesterol efflux from macrophages and hepatic paraoxonase 1 expression and activity. In clinical studies, dietary anthocyanin intake is associated with beneficial changes in serum biomarkers related to HDL function in a variety of human populations (e.g., in those who are hyperlipidemic, hypertensive, or diabetic), including increased HDL cholesterol concentration, as well as HDL antioxidant and cholesterol efflux capacities. However, clinical research on HDL functionality is lacking for some flavonoid subclasses (e.g., flavanols, flavones, flavanones, and isoflavones). Although there has been a tremendous effort to develop HDL-targeted drug therapies, more research is warranted on how the intake of foods or specific nutrients affects HDL function.